Rootless teeth: Dentin dysplasia type I - Sangamesh G Fulari; Deepti P Tambake (Wolters Kluwer Medknow Publications, 2013)
A rare case of hereditary disturbance of dentine, Dentin dysplasia type I is presented, which is characterized by short or total absence of roots, obliterated pulp chambers, and peri-apical radiolucencies. It affects both primary and secondary dentition. Management of patients with dentinal dysplasia is difficult and requires a multidisciplinary approach. An overview of dentin dysplasia and its management along with a case report is discussed.